Sintesis Etil Ester Dari Minyak Biji Kemiri (Aleurites molluccana) Menggunakan Metode Ultrasonokimia - Yunizar AL; Aisyah Aisyah; Suriani Suriani (Al-Kimia, 2015)
The availability of the fuel oil in the world are declining, so that alternative energy is needed to meet the needs of the fuel. One of the alternative energy is biodiesel (ethyl/methyl ester). The research aimed to determine the optimal conversion value of ethyl ester, to identify ester components and their concentration. The biodiesel was produced from candlenut oil (Aleurites mollucana) ethanol by the ratio of 1:6 using 0.5% KOH catalyst which reacted by utilizing ultrasonic wave (47 kHz) for 45, 60 and 75 minutes. Biodiesel conversion value were 3.9%, 1.6% and 1.2% respectively. The biodiesel obtained then were analyzed by FTIR and result the pattern of fatty acid ethyl esters. In addition, analysis by GC-MS revealed the concentration under variation times of ethyl palmitate, ethyl linoleic, ethyl oleic and ethyl stearic from variation time  45,  60  and  75 minutes. They were 6.34%, 1.76% and 1.56%), (25.94%, 6.46% and 7.46%), (31.42%, 8.17% and 8.79%) and 2.13%.